ANALISIS PENGARUH MUSIK GAME TERHADAP PENGALAMAN BERMAIN GAME GENSHIN IMPACT - Muhammad Ardiansyah; David Pramono (JURNAL ILMIAH BETRIK, 2022)
The main objective of this research is to determine the influence of music on games on the experience of playing the game genshin impact. This study uses experimental and qualitative research methods. The variables used in this research are Music (MU) and Video Game Experience (VGE) variables. In the experimental and qualitative methods, each researcher will select 30 people as respondents. The data collection technique used in the experimental research is to ask respondents to play the genshin impact game using music in the game and not using music in the game, then the researcher will provide questionnaires to the respondents, then for qualitative research the researcher will interview the respondents. Data analysis of both methods was carried out using the SPSS application and will be codified first. Based on the results of the experimental and qualitative data analysis that has been carried out, the authors conclude that the music variable influences the game playing experience variable